(untitled) (International Journal of Biology and Chemistry, 2023)
The most plentiful bioresource on earth is lignocellulosic biomass. The breakdown of lignocellulosic biomass attains different fermentable sugars which are considered to be very significant for the manufacturing of biogas, bioethanol etc. The major composition of lignocellulosic biomass is cellulose, lignin and hemicelluloses which are strongly linked with each other by hydrogen and covalent linkages thus generating a tough and rigid structure. The recalcitrant structure of lignin resists to solubilization thus arresting the degradation of cellulose and hemicelluloses present in bioplymeric structure. This addresses a striking challenge for the production of biofuels. To cope up with these limitations, immense research has been carried out for the development of pretreatment strategies. The present study utilized the alkaline pretreatment approach to digest cellulose, hemicelluloses and lignin content in locally available different agroindustrial wastes. This study employed Simultaneous Saccharification and Fermentation (SSF) process for bioethanol production from selected lignocellulosic biomass. Prior to fermentation all collected biomass was treated with 1% NaOH and then fermentation was carried out using Saccharomyces cerevisiae. The SSF was conducted at 30°C for 4-5 days. Along with pretreated biomass, untreated biomass was also subjected to SSF in order to compare the yield of bioethanol. The results of present research elaborate that pretreatment with 1% NaOH significantly degraded the complex polymeric structure of biomass hence induced enhanced production of bioethanol as compared to untreated agrowaste. Among all lignocellulosic biomass, pretreated banana peels attained higher production of bioethanol 118g/L with fermentation efficiency 139.75% and sugar utilization 97.9% than untreated banana peels achieved maximum ethanol production 42.4g/L with fermentation efficiency 53% and sugar utilization 68%. These findings indicate that before fermentation, a suitable pretreatment protocol must be applied to lignocellulosic substrates in order to increase the yield of ethanol and to meet the commercial needs.